For the Sake of a Song : Wangga Songmen and Their Repertories. - Marett, Allan. (Indigenous Music of Australia Series, 2013)
Wangga, originating in the Daly region of Australia's Top End, is one of the most prominent Indigenous genres of public dance-songs. This book focuses on the songmen who created and performed the song.